KEKERASAN SIMBOLIK DI MEDIA MASSA - Roekhan Roekhan (Fakultas Sastra Universitas Negeri Malang, 2010)
The research aims at reviewing the symbolic violence in mass media. The aspect of symbolic violence to be reviewed includes (a) the forms, (b) strategies, and (c) effects of symbolic violence to the reader. The research uses critical discourse analysis design developed by Fairclough. The result of data analyses found the realization of symbolic violence in the news text, in form of (a) blurred meaning, (b) bias logics, and (c) bias value. The blurred meaning, bias logics, and bias value as form of bias information in news text. The strategies of symbolic violence found in this research are (a) the softening of information, (b) information reasoning (logic), and (c) creating positive information. The effects of symbolic violence to the readers is seen in receptions of the information from the mass media includes (a) reception based on prejudice attitude and view and (b) reception based on neutral attitude. The symbolic violence does not impact to the readers reality in a short time respons